Analisis Buku Ajar Tematik untuk Mata Pelajaran PJOK Kelas III Berbasis Higher Order Thinking Skill - Seka Andrean (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2022)
The purpose of this research is to analyze the material in the thematic teaching book grade III Hots-based Elementary School. The method used is the library research approach through the source of the library of thematic teaching books (teacher's books and student books) grade III Curriculum 2013 Elementary School and from various other sources of literature. Then analyzed and presented the data findings objectively. The results of this research analysis show that the thematic teaching books (teacher's books and student books) in grade III Elementary School can already be said to be teaching material based on HOTS (Higher Order Thinking Skill) because more than 50% of the teaching materials presented already show high-level thinking criteria or HOTS.